In Search of Skills to Overcome Life's Obstacles in People Who Perform Supra-Personal Tasks - Zofia Remiszewska (Maria Curie-Skłodowska University, Lublin, Poland, 2024)
Introduction: In their lives, people have to cope with various limitations or obstacles. How they cope with such problems may determine their future and, thus, optimise or destroy their existence. Research Aim: The purpose of the research presented in this article was to identify the types of skills necessary to overcome life's obstacles in the biographies of those individuals pursuing supra-personal tasks who were able to face life's problems. Method: The qualitative paradigm approach was used. Data were extracted from an in-depth narrative interview, thus it was possible to understand the elements of the reality of the interviewed individuals related to their skills in overcoming life's obstacles. Results: The conducted research shows that the skills of overcoming life's obstacles identified in the participants were related to the existence of such traits as resilience, optimism, self-reliance and entrepreneurship. Conclusions: Possessing skills related to such qualities as resilience, optimism, self-reliance and entrepreneurship can make it easier for one to overcome obstacles and pursue one's goals, while strengthening one's self-esteem and self-confidence. It can cause the impossible to become possible.